Star formation in the local Universe from the CALIFA sample: I. Calibrating the SFR using integral field spectroscopy data - Catalan-Torrecilla, C. (2015)
The star formation rate (SFR) is one of the main parameters used to analyze the evolution of galaxies through time. The need for recovering the light reprocessed by dust commonly requires the use of low spatial resolution far-infrared data. The combination line luminosities provide an alternative, although uncertain dust-extinction corrections based on narrowband imaging or long-slit spectroscopy have traditionally posed a limit to their applicability. Integral field spectroscopy (IFS) is clearly the way to overcome this kind of limitation. Aims. We obtain integrated Hα, ultraviolet (UV) and infrared (IR)-based SFR measurements for 272 galaxies from the CALIFA survey at 0.005